The hermit crab's nose—antennal transcriptomics - Groh, Katrin C.; Vogel, Heiko; Stensmyr, Marcus C.; Grosse-Wilde, Ewald; Hansson, Bill S. (Frontiers in Neuroscience, 2014)
In the course of evolution, crustaceans adapted to a large variety of habitats. Probably the most extreme habitat shift was the transition from water to land, which occurred independently in at least five crustacean lineages. This substantial change in life style required adaptations in sensory organs, as the medium conveying stimuli changed in both chemical and physical properties. One important sensory organ in crustaceans is the first pair of antennae, housing their sense of smell. Previous studies on the crustacean transition from water to land focused on morphological, behavioral and physiological aspects but did not analyze gene expression. Our goal was to scrutinize the molecular makeup of the crustacean antennulae, comparing the terrestrial Coenobita clypeatus and the marine Pagurus bernhardus. We sequenced and analyzed the antennal transcriptomes of two hermit crab species. Comparison to previously published datasets of similar tissues revealed a comparable quality and GO annotation confirmed a highly similar set of expressed genes in both datasets. The chemosensory gene repertoire of both species displayed a similar set of ionotropic receptors (IRs), most of them belonging to the divergent IR subtype. No binding proteins, gustatory receptors (GRs) or insect-like olfactory receptors (ORs) were present. Additionally to their olfactory function, the antennules were equipped with a variety of pathogen defense mechanisms, producing relevant substances on site. The overall similarity of both transcriptomes is high and does not indicate a general shift in genetic makeup connected to the change in habitat. Ionotropic receptors seem to perform the task of olfactory detection in both hermit crab species studied.